Methods for estimating forest income and their challenges - Wollenberg, Eva Karoline (2000)
Income measures are increasingly used as an indicator of the well-being of forest villagers, their use of forest products, and even the value of a forest. The methods for estimating income are often underreported, however, and little analysis is available of the methods required to measure income. Ten case studies are examined to demonstrate methods in use for quantifying household income. The cases are used to investigate techniques for overcoming two common methodological obstacles: (1) the cost of collecting data about many, diverse and distant sources of income from the forest, and (2) the difficulty of aggregating the monetary values of products. The strengths and weaknesses of the techniques are discussed to help researchers identify methods appropriate to their needs. The article concludes that: (1) costs are most effectively reduced where the number of products studied is limited and methods based on indirect observation are used; (2) aggregating the monetary value of a mix of market and subsistence products requires sensitivity to the limitations of the methods; and (3) addressing the diversity of values that forest products provide to people might provide a more accurate estimation of income.